Tenecteplase for Acute Ischemic Stroke Treatment - Baird, Alison E.; Jackson, Richard; Jin, Weijun (Seminars in Neurology, 2021)
The introduction of thrombolytic therapy in the 1990s has transformed acute ischemic stroke treatment. Thus far, intravenous recombinant tissue plasminogen activator (rt-PA) also known as alteplase is the only thrombolytic proven to be efficacious and approved by the United States Food and Drug Administration. But the thrombolytic agent tenecteplase (TNK) is emerging as a potential replacement for rt-PA. TNK has greater fibrin specificity, slower clearance, and higher resistance to plasminogen activator inhibitor-1 than rt-PA. Hence, TNK has the potential to provide superior lysis with fewer hemorrhagic complications. Also, easier bolus-only administration makes TNK a very practical rt-PA alternative. In several clinical trials, TNK has shown similar efficacy and safety to rt-PA, and the potential to be at least noninferior to rt-PA in some settings. TNK may be superior to rt-PA for reperfusing large vessel occlusions in patients with salvageable penumbra, although this has not yet translated to improved clinical outcomes. Further phase 3 studies are in progress comparing rt-PA with TNK for acute ischemic stroke during the first 4.5 hours. Studies are also in progress to evaluate the use of TNK for extended applications, such as wake-up stroke.
Keywords: stroke; treatment; tenecteplase; alteplase; recombinant tissue plasminogen activator; intravenous thrombolysis